Detail specification for multi-contact rectangular electrical connectors with moulded bodies for d.c. and low frequency applications. Unsealed with end guides or jackscrew couplings and front release, rear removable crimp contacts. Full assessment level. (15th October 1981) - British Standards Institution,
No abstract available